2010
DOI: 10.5851/kosfa.2010.30.1.42
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Various Cooking Methods on Quality Characteristics of Korean Boiled Pork (Soo-yuk)

Abstract: This research was conducted to evaluate the effects of cooking conditions on quality characteristics of Soo-Yuk, a traditional Korean food. The cooking conditions were as follows: boiled until the core temperature of a sample in (T3) showed the longest cooking time, the lowest cooking yield and moisture content, and the highest shear force. The instrumental color showed a significant difference among the cooking conditions. The sarcomere length of soo-yuk boiled in 100 o C water (T3) was the shortest, but the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…These contrasting results could be attributed due to the increased moisture content during smoking, which is caused by a hard coating that forms on the meat surface and reduces cooking loss ( Table 2 ). Chae and Kim (2010) reported that high temperature and long cooking time produces lower moisture content in boiled pork. According to Chae (2011) , the moisture content in boiled pork is influenced by cooking methods such as boiling and steaming.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…These contrasting results could be attributed due to the increased moisture content during smoking, which is caused by a hard coating that forms on the meat surface and reduces cooking loss ( Table 2 ). Chae and Kim (2010) reported that high temperature and long cooking time produces lower moisture content in boiled pork. According to Chae (2011) , the moisture content in boiled pork is influenced by cooking methods such as boiling and steaming.…”
Section: Resultsmentioning
confidence: 99%
“… Chae and Kim (2010) reported that high temperature and long cooking time produces lower moisture content in boiled pork. According to Chae (2011) , the moisture content in boiled pork is influenced by cooking methods such as boiling and steaming. However, Hyon et al .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations